Pengaruh Urutan Pemberian Materi Pembelajaran (Sequenced) Dengan Model Fragmented dan Model Connected Terhadap Hasil Belajar Siswa Pada Konsep Vektor Di SMA Negeri 1 Palu - Muhsina Muhsina; I Komang Werdhiana; Marungkil Pasaribu (Mitra Sains, 2015)
The present research is an experimental research studies about the effect of presenting sequenced learning material on the concept of vector through fragmented and connected learning model. The subject of the research consists of 30 students of grade XA who were treated with fragmented model and 30 students of grade XB who were treated with connected model. The data of the two groups of subject were analyzed by using t-test with 5% real level. The result of the experiment indicates that thitung (4,02) is out of acceptance area (2,66). The result indicates that there is the difference result of the students’ learning on concept of vector between those who taught by using fragmented and connected model. Quantitatively, the average score of the students who were treated by using fragmented model is 73, 56 and those who were treated by using connected model is 61,78, it then can be inferred that the fragmented learning model is more effective than connected model use to present the lesson.